Work-Life Balance of Employees in Bulgarian Service Sector Companies - Kovacheva, Siyka; Kabaivanov, Stanimir (Calitatea Vieții, 2008)
The paper presents some of the main challenges in front of the work-life balance of employees in the developing service sector in Bulgaria. The overall satisfaction is measured using regression analysis of survey data collected in 2007 from four companies – a supermarket, telecom firm, bank and hospital. Individual experiences of managing family and work life are influenced by the structural and cultural supports and constraints at the workplace and the household. Working organisations can increase employees’ satisfaction by providing more opportunities for team work and flexible schedules, developing a family friendly organisational culture and offering assistance with childcare.